1997
DOI: 10.1002/(sici)1097-4644(1997)28/29+<90::aid-jcb10>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Genes differentially expressed with malignant transformation and metastatic tumor progression of murine squamous cell carcinoma

Abstract: Molecular changes occurring with tumor formation and metastasis need to be identified in order to define novel markers and targets for chemoprevention and therapy. Cell lines from a multistage model of murine squamous cell carcinoma were analyzed for differences in gene expression using mRNA differential display. mRNA was isolated from primary keratinocytes, an in vitro transformed keratinocyte line (Pam 212), and three metastatic cell lines derived from Pam 212 following tumor progression in vivo. cDNA was sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 46 publications
(38 reference statements)
1
17
0
Order By: Relevance
“…We previously detected increased expression of KC mRNA encoding murine GRO-a by di erential display in SCC reisolated from lymph node and lung following metastatic tumor progression of the in vitro transformed keratinocyte line PAM 212 (Dong et al, 1997). Figure 1a shows a Northern blot analysis con®rming that KC mRNA expression is increased in representative PAM LY and LU cell lines reisolated from lymph node and lung metastases when compared with normal BALB/c and transformed PAM 212 keratinocytes.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…We previously detected increased expression of KC mRNA encoding murine GRO-a by di erential display in SCC reisolated from lymph node and lung following metastatic tumor progression of the in vitro transformed keratinocyte line PAM 212 (Dong et al, 1997). Figure 1a shows a Northern blot analysis con®rming that KC mRNA expression is increased in representative PAM LY and LU cell lines reisolated from lymph node and lung metastases when compared with normal BALB/c and transformed PAM 212 keratinocytes.…”
Section: Resultsmentioning
confidence: 86%
“…We found that KC mRNA and protein was uniformly expressed at high concentration by 15/15 cell lines reisolated from lymph node and lung metastases of the murine SCC line PAM 212 (Smith et al, 1998). These reisolated metastatic cells, exhibited an increased potential for growth and metastasis in vivo when compared with the low KC expressing PAM 212 cell line Dong et al, 1997). Conversely, clones of PAM 212 which expressed no detectable KC by ELISA grew even more slowly than the low KC expressing PAM 212 cell line (Smith et al, 1998).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…In contrast, Sp17 mRNA could not be detected in normal somatic tissues, suggesting the restricted normal tissue expression of Sp17 [18,25]. Expression of Sp17 in malignant cells was first discovered by Dong et al [26]. High expression of the mouse homologue Sp17 was observed in metastatic cell lines derived from a murine model of squamous cell carcinoma but not in the non-metastatic parental line.…”
Section: Sperm Protein 17 (Sp17) As a New Member Of Ct Antigensmentioning
confidence: 99%